Clinical and laboratory profile of dengue fever in children in a tertiary care hospital of Navi Mumbai, India - Bhat, Minakshi; Otiv, Anjali (International Journal of Contemporary Pediatrics, 2020)
Background: Dengue fever is a mosquito born arboviral illness endemic in tropical countries and causes significant mortality and morbidity due to lack of definitive treatment. The objective of this study was to assess the clinical and laboratory profile of confirmed cases of dengue in children up to 12 years of age and also to charactrise the risk factors for severe dengue. Methods: This is a descriptive, observational, retrospective study done in the Department of Pediatrics, Terna Medical College, Nerul, Navi Mumbai, India. Medical records of all children up to 12 years of age diagnosed to have dengue were reviewed. Their clinical and laboratory profile were recorded in a pro forma and analyzed. All cases were classified as per WHO guidelines into non severe and severe dengue cases. Results: Among the 117 confirmed dengue cases, (84.6%) had non severe dengue and (15.4%) had severe dengue. The most common age group affected was 9-12 years (45.3%) with a male to female ratio of 2.4:1. Fever was the most common clinical feature seen in all cases followed by headache (83%), myalgia (81%), ascites (24.7%), vomiting (17.9%). Clinical signs of ascitis, hepatomegally, gastrointestinal bleeding, pleural effusion and shock were predominantly associated with severe dengue cases. Laboratory parameters showed leukopenia in 58.1% and thrombocytopenia (platelet counts <20,000/cumm3) in16.2% cases. Elevated liver enzymes, raised hematocrit (36.3%) and coagulation abnormalities were seen in over 50% dengue cases and were significantly associated with severe dengue dengue. Conclusions: Knowledge of clinical and laboratory profile of dengue cases of a particular area will help in early prediction of risk factors for severe dengue resulting in favourable outcome of such cases.